Causes and Characteristics of Infidelity in Primary Class Students - Gapparovna, Ibragimova Shakhnoza; Alievich , Ergashev Eminjon; Oribovna , Rakhmonova Ayshakhan (International Journal of Membrane Science and Technology, 2023)
The article presents the study of the causes of non-learning by primary school students by psychologists and their analysis, experimental analysis of the reasons from the point of view of teachers.